Development of a Selective Agar for the Detection of Probiotic Strain Ligilactobacillus animalis NP51 and Other Lactic Acid Bacteria in Cattle Feed - Kasey Thompson; Shamima Akter; Naola Ferguson-Noel; John J. Maurer; Margie D. Lee (Agriculture)
The enormous potential of bacteriotherapy in disease treatment and prevention has created a large probiotic market. Significant challenges exist in assessing probiotic quality, efficacy and viability. Lactic acid bacteria (LAB) are commonly used probiotics and the most abundant of the vertebrate microbiota. The goal of this study was to make MRS agar specific for probiotic Ligilactobacillus animalis NP51, since the current formulation is not sufficiently selective. Here, 53 chemicals were screened to identify compound(s) that reduced the growth of non-LAB and fungi on de Mann, Rogosa, and Sharpe (MRS) agar, and which were selective for LAB and specifically the probiotic strain NP51. Cattle feed was selected as the sample type, as it is commonly amended with Lactobacillus or yeast probiotics and often includes silage, a diverse microbial consortium of fungi and LAB. Modified MRS was evaluated for its effectiveness in determining probiotic viability and the detection of L. animalis NP51 in cattle feed, amended with this probiotic. qPCR was used to specifically detect and enumerate NP51 in commercial and experimental feed samples. For four selective agents, nystatin, guanidine hydrochloride, CuSO4, and ZnCl, it was identified that when used together, they reduced the growth of bacteria and fungi, but did not inhibit the Lactobacillus probiotic NP51 and other LAB. Metagenomic analysis revealed LAB as the major group cultivated on modified MRS agar from the plating of cattle feed amended with silage. As an enrichment, modified MRS broth improved the qPCR detection of probiotic strain NP51. This study illustrated that improvements can be made to existing bacteriological media for enumerating probiotic NP51 and determining the product’s viability.